Acute and chronic responses of denitrifying culture to diclofenac. (January 2015) - Ozdemir, Gamze; Aydin, Egemen; Topuz, Emel; Yangin-Gomec, Cigdem; Okutman Tas, Didem
Graphical abstract: Highlights: Continuous diclofenac amendment resulted in a decrease in the gas production. Diclofenac removal in diclofenac-acclimated culture was less than 15%. N2 O reduction was negatively affected in the presence of diclofenac at low SRT. Diclofenac resulted in a decrease in nitrate removal rate especially at low SRT. Abstract: Acute and chronic effect as well as biodegradation potential at different sludge retention times (SRTs) of a priority pollutant, diclofenac on denitrification process was assessed. The continuous amendment of the culture for 6 months with 1 μg/L diclofenac resulted in 30% decrease in gas production. The average diclofenac removal observed in the diclofenac-acclimated culture was less than 15%. Batch tests showed that nitrate was removed in diclofenac free-control reactor at a higher rate compared to diclofenac amended reactor. Although, SRT did not have any progressive effect on diclofenac degradation, the system operated at low SRT was more sensitive to diclofenac and resulted in an increase in N2 O emission. Wastewater treatment plants (WWTPs) operated at higher SRTs may tolerate and recover from the adverse effects of such micropollutants. The study can lead to other researchers to understand the fate and effect of other emerging pollutants in the anoxic unit of WWTPs.